(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Artificial Intelligence (AI) is fundamentally reshaping the healthcare landscape, profoundly impacting diagnostics, treatment, and patient care. AI technologies such as machine learning, natural language processing, and computer vision have enabled healthcare providers to harness vast amounts of data for enhanced decision-making. This capability has significantly improved diagnostic accuracy by identifying subtle patterns and correlations in patient data, leading to earlier detection of diseases and more targeted treatment strategies. Additionally, AI-driven predictive analytics are revolutionizing healthcare operations, facilitating proactive management of resources, predicting disease outbreaks, and optimizing hospital workflows. AI is revolutionizing patient care through innovations like virtual health assistants, remote monitoring systems, and personalized medicine platforms. These advancements empower patients with continuous health monitoring and personalized treatment plans, promoting proactive management of health conditions and improving overall patient outcomes. However, the integration of AI into healthcare presents challenges such as ensuring data privacy, navigating regulatory frameworks, and addressing the need for healthcare professionals to acquire proficiency in AI technologies. the review of AI’s impact on the healthcare sector underscores its transformative potential to enhance diagnostic precision, personalize patient care, and optimize healthcare delivery. By critically examining these advancements, we highlight AI’s role in reshaping the future of healthcare, offering unprecedented opportunities to improve efficiency, quality of care, and patient satisfaction.